Addressing the Exorbitant Cost of Labeling Medical Images with Active Learning - Rahimi, Saba; Oktay, Ozan; Alvarez-Valle, Javier; Bharadwaj, Sujeeth (International Conference on Machine Learning in Medical Imaging and Analysis, 2021)
Successful application of deep learning in medical image analysis necessitates unprecedented amounts of labeled training data. Unlike conventional 2D applications, radiological images can be three dimensional (e.g. CT, MRI) consisting of many instances within each image. The problem is exacerbated when expert annotations are required for effective pixel-wise labeling, which incurs exorbitant labeling effort and cost. Active Learning is an established research domain that aims to reduce labeling workload by prioritizing a subset of informative unlabeled examples to annotate. Our contribution is a cost-effective approach for U-Net 3D models that uses Monte Carlo sampling to analyze pixel-wise uncertainty. Experiments on the AAPM 2017 lung CT segmentation challenge dataset show that our proposed framework can achieve promising segmentation results by using only 42% of the training data.
Best Presentation Award